Analysis Characterization of Main Character in Movie “Role Play 2024” - Ni Putu Lusi Desya Wardani; Gede Irwandika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This study analyzed the complex characterization of Emma and Dave in the 2024 film Role Play using qualitative descriptive methods. By employing Morner and Rausch's (1998) characterization techniques and Gale's (2017) personality type theory, the research examined how the characters' dual identities and internal conflicts enriched the film's narrative. The primary data source was the film itself, which was thoroughly analyzed through content analysis. The findings revealed Emma as a dynamic character leading a double life: she was both a devoted wife and a skilled assassin. Her internal struggles and the emotional toll of her secret profession added depth to her role. In contrast, Dave, initially portrayed as a trusting and supportive husband, evolved into a character marked by growing suspicion and frustration, while remaining steadfast in his loyalty to his family. The study concluded that the nuanced portrayal of Emma and Dave significantly enhanced the film's narrative engagement and the viewer's emotional connection. These characterizations provided innovative insights into character development in cinematic storytelling, offering a comprehensive framework for future research in similar genres.